Lactobacillus reuteri DSM 17938 for managing infant colic: protocol for an individual participant data meta-analysis. Issue 12 (4th December 2014) - Sung, Valerie; Cabana, Michael D; D'Amico, Frank; Deshpande, Girish; Dupont, Christophe; Indrio, Flavia; Mentula, Silja; Partty, Anna; Savino, Francesco; Szajewska, Hania; Tancredi, Daniel
Abstract : Introduction: Infant colic, or excessive crying of unknown cause in infants less than 3 months old, is common and burdensome. Its aetiology is undetermined, and consensus on its management is still lacking. Recent studies suggest a possible link between infant colic and gut microbiota, indicating probiotics to be a promising treatment. However, only a few strains have been tested, and results from randomised controlled trials are conflicting. It is important to clarify whether probiotics are effective for treating infant colic in general, and to identify whether certain subgroups of infants with colic would benefit from particular strains of probiotics. Methods and analysis: Through an individual participant data meta-analysis (IPDMA), we aim to identify whether the probiotic Lactobacillus reuteri DSM 17938 is effective in the management of infant colic, and to clarify whether its effects differ according to feeding method (breast vs formula vs combined), proton pump inhibitor exposure, and antibiotic exposure. The primary outcomes are infant crying duration and treatment success (at least 50% reduction in crying time from baseline) at 21 days postintervention. Individual participant data from all studies will be modelled simultaneously in multilevel generalised linear mixed-effects regression models to account for the nesting of participants within studies. Subgroup analyses of participant-level and intervention-level characteristics will be undertaken on the primary outcomes to assess if the intervention effect differs between certain groups of infants. Ethics and dissemination: Approved by the Royal Children's Hospital Human Research Ethics Committee (HREC 34081). Results will be reported in a peer-reviewed journal in 2015. Trial registration number: PROSPERO CRD42014013210.